Seven Fundamental Principles in the Effectuation of Recursion - Saxena, Rishi (International Journal of Computer Sciences and Engineering, 2019)
Recursion is a programming methodology used to write efficient computer programs. A recursion based solution to a given programming problem can be translated to an iteration based solution or by using some other programming constructs which do not accord with the methodology of recursion. Computer programmers and software engineers usually face this kind of confusion that which methodology to implement in a particular case or to some specific problem class as there are no candid guidelines regarding the implementation of recursive solution, leaving the developers in a state of taking decisions upon their choices and preferences. This paper explores the issue of recursion in various aspects of developing a computer program and discovers the seven fundamental principles behind the use and implementation of recursion in generating a solution for a problem of specific nature and class. These seven principles can be referred as pillars of foundation on which recursion is employed by many programmers as a tool to generate an effective solution which adheres to the quality standards of software engineering.